Extreme Rainfall-Producing Echo Training Processes During Two Landfalling Typhoons in East China - Zhimei Weng; Wen Gu; Kai Wang; Li Gao; Yecheng Feng; Boyan Lu; Qiao Lu; Sinan Gu (Advances in Meteorology)
Echo training represents the primary mechanism through which rain bands precipitate extreme rainfall events. This study employed a combination of observational data and ERA5 reanalysis data to examine two instances of “echo training” that occurred following the landfall of typhoons Soudelor (2015, Process 1) and Fitow (2013, Process 2) in China. The findings indicate notable differences in the environmental background, characteristics, and the organization of convective rainbands between these two “echo training” processes. During Process 1, a well-developed convective system accompanied by a deeper boundary layer convergence between the cold pool and the easterly flow is observed. The presence of baroclinic structures permits the uplift of warm and humid air from the ocean that facilitated by the solenoidal term. During this period, the dispersion queues on both sides of the rainband contributed to the strengthening of convection and enabled convective cells to traverse the length of the rainband for an extended duration. In Process 2, the comparative wind between the easterly flow and the weak cold pool resulted in relatively shallow convergence, while the warm rain process dominated. The continuous generation of new cells occurred at the eastern boundary of the rainband, while dissipation occurred at the western boundary, resulting in persistent heavy rainfall for the covered area.